Wound Degrees and Body Image in Diabetes Mellitus Patients with Diabetic Foot Ulcers - Zatihulwani, Eliza Zihni; Prawito, Prawito; Sasmito, Nanang Bagus (Fakultas Kedokteran, 2024)
Diabetic ulcers are one of the serious complications that can cause open wounds and infections in the feet and other parts of the body. Sufferers often feel uncomfortable, lose self-confidence, and even fear amputation. The purpose of this study was to determine the relationship between wound severity and body image in diabetic ulcer patients. This study used a correlational analytical design through a cross-sectional approach. The population in this study were 37 diabetic ulcer patients using a purposive sampling technique and a sample of 34 respondents. The instruments used were observation sheets and questionnaires. Data analysis used Spearman rank, the time of the study was conducted in December 2023. Based on the results of the study, it was found that the degree of the wound showed that most of the respondents had deep ulcers as many as 20 people (58.8%). Body image in diabetic ulcer patients showed that most of the respondents had a body image in the sufficient category as many as 23 people (67.7%). There is a relationship between the degree of injury and body image in diabetic ulcer patients with a p value of 0.004 (